2014
DOI: 10.1037/xap0000016
|View full text |Cite
|
Sign up to set email alerts
|

Producing a commentary slows concurrent hazard perception responses.

Abstract: Commentary driver training involves teaching drivers how to verbally acknowledge their perceptual and cognitive processes while driving, and has been shown to improve performance in driving-related tasks. However, those studies demonstrating benefits of commentary training have not done so under conditions of live commentary, which is the typical protocol used with advanced drivers. In the current study we present the results of 2 experiments that show that producing a commentary can actually slow responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…According to a paper accepted in JEPA, listening to commentaries can negatively affect eye movements (Young, Chapman and Crundall 2014). Perhaps the benefit to experts of the extra information outweighs the costs, but is the opposite true for novices?…”
Section: Discussionmentioning
confidence: 99%
“…According to a paper accepted in JEPA, listening to commentaries can negatively affect eye movements (Young, Chapman and Crundall 2014). Perhaps the benefit to experts of the extra information outweighs the costs, but is the opposite true for novices?…”
Section: Discussionmentioning
confidence: 99%
“…Not only do trainees produce on-road commentaries with supervision, they are also able to use commercially available DVDs that demonstrate an expert commentary and suggest that the viewer carry out their own on-road commentaries (Gilbert, 2007). Young et al (2014) found that when commentary exposure is followed by production of a driving commentary during a hazard perception test, hazard perception response times are significantly longer than in a control group that was neither exposed to commentary nor producing a commentary at test. This has important implications for commentary driver training, suggesting that trainees should not be encouraged to perform their own commentary on the road without expert supervision.…”
Section: Introduction Commentary Driving Involves Producing a Continumentioning
confidence: 99%
“…Since commentary driving involves talking about the contents of the visual scene, which should be attended to for hazard perception, one might expect the demands to be lower than other types of conversation but a detriment is still observed (Young et al, 2014). In order to establish whether the detriment of a live commentary is specific to producing a commentary following an earlier example or caused by any speech about the visual scene while searching for hazards we can compare the effects of producing a commentary after exposure to those of producing a naïve commentary, based on only limited instruction without commentary exposure.…”
Section: Introduction Commentary Driving Involves Producing a Continumentioning
confidence: 99%
See 2 more Smart Citations